2009
DOI: 10.1111/j.1365-2966.2009.15365.x
|View full text |Cite
|
Sign up to set email alerts
|

Origin and structure of the Galactic disc(s)

Abstract: We examine the chemical and dynamical structure in the solar neighbourhood of a model Galaxy that is the endpoint of a simulation of the chemical evolution of the Milky Way in the presence of radial mixing of stars and gas. Although the simulation's star-formation rate declines monotonically from its unique peak and no merger or tidal event ever takes place, the model replicates all known properties of a thick disc, as well as matching special features of the local stellar population such as a metal-poor exten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
299
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(317 citation statements)
references
References 28 publications
14
299
1
Order By: Relevance
“…Therefore, we argue that a pre-existing thick disc at the time of bar formation, whether as part of a continuum with the thin disc (Brook et al 2004;Schönrich & Binney 2009;Loebman et al 2011;Bird et al 2013;Bovy et al 2012), or as the separate distinct structure envisaged by Bekki & Tsujimoto (2011), is not necessary to produce the chemical trends observed in the Milky Way bulge. However, it is not inconceivable that the oldest population evolves into what, structurally, is consistent with the present-day thick disc.…”
Section: Is a Thick Disc Necessary?mentioning
confidence: 99%
“…Therefore, we argue that a pre-existing thick disc at the time of bar formation, whether as part of a continuum with the thin disc (Brook et al 2004;Schönrich & Binney 2009;Loebman et al 2011;Bird et al 2013;Bovy et al 2012), or as the separate distinct structure envisaged by Bekki & Tsujimoto (2011), is not necessary to produce the chemical trends observed in the Milky Way bulge. However, it is not inconceivable that the oldest population evolves into what, structurally, is consistent with the present-day thick disc.…”
Section: Is a Thick Disc Necessary?mentioning
confidence: 99%
“…Several works (e.g., Loebman et al 2011;Schönrich & Binney 2009b) have also proposed that radial migration can give rise to thick disc formation by bringing out high-velocity-dispersion stellar populations from the inner disc and the bulge. More detailed dynamical studies Minchev et al 2012a;Vera-Ciro et al 2014) have more recently shown that migration does not contribute to any significant level to disc thickening, but on the opposite, it suppresses flaring when external perturbations are included (Grand et al 2016;Minchev et al 2014a).…”
Section: The Galactic Thick Discmentioning
confidence: 99%
“…Such a scenario was used, for example, in the analytical model of Schönrich & Binney (2009b), where the authors claimed to explain the Milky Way thickand thin-disc characteristics (both chemical and kinematical) without the need of mergers or any discrete heating processes. Similarly, the increase of disc thickness with time found in the simulation by Roškar et al (2008) has been attributed to migration in the work by Loebman et al (2011).…”
Section: Migration and Disc Thickeningmentioning
confidence: 99%
“…• a recent suggestion is that stars on more energetic orbits migrate out from the inner galaxy to form a thick disk at larger radii where the potential gradient is weaker (Schönrich & Binney, 2009) How can we test between these possibilities for thick disk formation? Sales et al (2009) looked at the expected orbital eccentricity distribution for thick disk stars in different formation scenarios.…”
Section: The Formation Of the Thick Diskmentioning
confidence: 99%